Dot-to-well transitions in InAs/InGaAs dots-in-a-well probed via photocurrent and electroluminescence spectroscopy - Defensor, Michael J.
Hole states of InAs/InGaAs dots-in-a-well (DWELL0 are probed indirectly by observing inter-Quantum Well-QuantumDot (inter-QW-QD) transitions through photocurrent (PC) and low temperature electroluminescence (LT-EL) spectroscopy. We find multiple sharp peaks have spacing in the range of 10-20meV in between the expected quantum dot (QD) and the quantum well (QW) signals. Our results show that these features are due to transitions between the QW electron ground state energy level and the confined hole states of the QDs. It is worthwhile to note that prior to this work there has been no documented research observing transitions of this type. The QD hole level energy spacings are found to be within range of the hole level spacings derived through 8-band k.p theoretical methods. The transitions also fall within the range of values experimentally deduced from photoluminescence excitation (PLE) experiments. The data extracted from these transitions provide experimental values for the QD hole confinement energies which can potentially aid in verification of theoretical models in QD structures.